THE INFLUENCE OF PRODUCT DESIGN AND PRICE ON THE DECISION TO PURCHASE ADIDAS SHOES (Case Study in Bengkulu City Community) - Anggi Josetio Prayoga; Alek Sulaiman Efindi; Emy Heriyanto; Rian Nespia (Journal of Research in Social Science and Humanities, 2024)
This research aims to determine the influence of product design and Price on purchasing decisions for Adidas shoes (case study in the people of Bengkulu City). This research uses a quantitative approach. This research was conducted on the people of the city of Bengkulu. The population used in this research was all the people of Bengkulu who knew and were familiar with Adidas brand shoe products. The sample in this study consisted of 75 respondents using the accidental sampling method. Data collection techniques in this research used observation, interviews, and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis, Classical Assumption Test, t-test and F Test. The results of this research show that the Product Design variable partially has a significant influence on the decision to purchase Adidas shoes with a significance value of 0.005 0.05; the price variable partially has a considerable influence on the decision to purchase Adidas shoes with a significance value of 0.016 0.05, then the product design and price variables simultaneously have a significant influence on the decision to purchase Adidas shoes with a significance value of 0.000 0.05.